13 Risk Documentation in Consent Form of Open Inguinal Hernia Repair. (28th February 2022) - Hassan, M.
Abstract: Introduction: Inguinal hernia repair is amongst the most commonly performed general surgical operations. The high case load of groin repair in our hospital has the potential to have high risk of medical legal complications. The importance of discussing these potential complications with patients, allowing them to make informed decisions about their care, and clearly documenting them during the consent process, is clear. Aim: We aimed to assess the quality and consistency of consent forms for open inguinal hernia repairs with emphasis on the risks being documented. Objectives: Measure the compliance of Trust consent forms with (RCS) and British Hernia Society (BHS) 2016 guidelines and European Hernia Society (EHS) International guidelines for Groin Hernia Management (2019). Method: Retrospective consent form analysis was carried out for all (38) open inguinal hernia repairs done during July-September 2020. The documentation of 13 pre-determined risks, was analysed, some specific to open inguinal hernia repairs, others general surgical complications. Results: A total of 38 Trust consent forms were audited. Infection (100%) and bleeding (95%) were the most commonly documented risks. The documentation of chronic infection/abscess formation (5%), numbness (60%), testicular atrophy (31%) and scarring (34%) all increased compared to the two previous audit phases, the latter two significantly so. Unfortunately, many of the risks audited (8/13) showed a decrease in compliance with documentation with only two of the examined risks meeting the standard or 'partially' meeting it. Notably, recurrence and damage to other structures documentation dropped by over 10% (17% drop and 31% drop, respectively).